Edukasi SWADAIA: Swamedikasi Dispepsia Berbasis Kasus dan Video pada Masyarakat Desa Sungai Kakap, Kabupaten Kubu Raya: SWADAIA Education: Case and Video Based Dyspepsia Self-Medication in the Sungai Kakap Village Community, Kubu Raya Regency - Najini, Robby; IH, Hariyanto; Kurniawan, Hadi; Nugraha, Fajar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The prevalence of dyspepsia in Sungai Kakap Village is ranked third largest based on data from the Sungai Kakap Community Health Center, Kab. Kubu Raya with an incidence of 1,636 cases in 2023. One of the problems experienced by dyspepsia patients is inappropriate self-medication or self-medication. This Community Service Activity (PKM) is aimed at PKK members and Posyandu cadres because they are part of the community and are also an extension of health workers in helping solve problems experienced by dyspepsia patients. The method used in this PKM is case-based and educational videos. This PKM activity consists of several activities including preparation of activities; orientation and coordination of activities; selecting the target audience for educational media creation activities; providing pre-tests and cases at the beginning of activities; providing educational materials; discussion; post-test; evaluation of activity implementation; and data analysis. The output of this community service is publication in local electronic media in West Kalimantan (Suara Pemred/Tanjungpura Times), publication of scientific articles in the Sinta 4 accredited journal